Miłość, wierność i odpowiedzialność w przestrzeniach spotkań młodzieży studiującej - Ściupider-Młodkowska, Mirosława (Studia Edukacyjne, 2020)
Ściupider-Młodkowska Mirosława, Miłość, wierność i odpowiedzialność w przestrzeniach spotkań młodzieży studiującej [Love, Loyalty and Responsibility in Meeting Spaces of University Students]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 235-251. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.13 Intimate partner relations have been an important research topic for years in the social sciences that address the order and survival of families and future generations. It is worth considering the contemporary code and the model of love and intimacy, which is just as natural in the process of socialization as the binding partnership for a lifetime. The purpose of the article is not to answer the question about the norm and the pathology in partner relations. In the assumption of the questions taken up, several issues have been raised in the field of constructivism and the phenomenon of partnership transformations and models of love, fidelity and responsibility in environments such as the family and parallel contemporary environments, such as virtual media in the form of the Internet and other determinants of popular culture. The discourse on emotional capitalism in partner relations raises numerous questions, constituting the theoretical basis of the questions addressed in this article: Do modern shortterm relationships determine the feeling of love and loyalty as a currency in the era of the Self? How far does the contemporary individualization of life change being together? Does pedagogical and psychological expertise provide real help in finding genuine values? Are they a response to loneliness, fear and contemporary consumerism in love relationships?